The Use of Plastic Sack Fiber and Rice Husk Ash in Increasing the California Bearing Ratio (CBR) Value on the Girisubo Road Section Gunung Kidul Regency - Rizky Praja, Riandana; Riyanto, Agus (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
Soil conditions in the Girisubo area, Gunung Kidul Regency, have low soil bearing capacity, so road infrastructure is bumpy and landslides. Therefore, the soil in the area needs to be stabilized and looking for bearing capacity of the soil before use for road subgrades. Clay can be improved by various soil improvement methods, including testing, by mixing plastic sack fiber and rice husk ash. These materials are used based on the high availability of plastic waste and rice husk waste, which are piling up every year. The additional material used was plastic sack fiber with variations of 0.1%, 0.2%, and 0.3% in rice husk ash variations of 0%, 2%, 4%, 6%, and 8% of the dry weight of the soil with the number of test objects 15 pieces. Based on the results, it found the highest CBR value change was obtained in the composition of a mixture of 0.3% plastic sack fiber and 4% rice husk ash of 18.49% and able to increase the percentage of the soil CBR value by 201.50% from the original soil value of 6,13%. Using plastic sack fiber and rice husk ash with the appropriate composition can increase the CBR value and have good quality.